The phyllosphere microbiome and its potential application in horticultural crops. A review - Barrera, Silvia E.; Sarango-Flóres, Stalin-Wladimir; Montenegro-Gómez, Sandra-Patricia (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Microorganisms are essential for life on Earth. They are found in different environments and conditions, such as pH, temperature, pressure, and humidity, etc. In natural and agricultural ecosystems, nutrient cycling and plant protection are important roles played by microorganisms associated with plant species. However, the mechanisms to colonize those environments are not fully understood. This mini-review describes bacterial communities associated with the phyllosphere and an agricultural approach for potential applications. In the context of foodborne illnesses and losses in agricultural production, important issues have arisen because of pathogen attacks. On the other hand, the use of beneficial microorganisms in agriculture is an alternative for improving plant growth, health and production. In this sense, growth promoting bacteria and biocontrol agents isolated from the phyllosphere of several plant species have been less exploited than those from the soil or rhizosphere. However, the treatment of some plant diseases, reduction in pathogen incidence and nitrogen fixation in natural and agricultural systems are successful examples. In the context of food safety, a better understanding of how the indigenous phyllosphere microbiota enable plants to protect themselves against pathogens and to acquire nutrients is expected to prove its importance in the agricultural field. Microbial sources can be managed to reduce the use of chemical products and could be used as an alternative of agronomical applications for improving agroecosystem productivity.